Understanding how high stocking densities and concurrent limited oxygen availability drive social cohesion and adaptive features in regulatory growth, antioxidant defense and lipid metabolism in farmed gilthead sea bream (Sparus aurata) - Holhorea, Paul G.; Naya-Català, Fernando; Belenguer, Álvaro; Calduch-Giner, Josep A.; Pérez-Sánchez, Jaume (Frontiers in Physiology, 2023)
The study combined the use of biometric, behavioral, physiological and external tissue damage scoring systems to better understand how high stocking densities drive schooling behavior and other adaptive features during the finishing growing phase of farmed gilthead sea bream in the Western Mediterranean. Fish were grown at three different final stocking densities (LD, 8.5 kg/m3 ; MD, 17 kg/m3 ; HD, 25 kg/m3 ). Water oxygen concentration varied between 5-6 ppm in LD fish to 3-4 ppm in HD fish with the summer rise of water temperature from 19°C to 26°C (May-July). HD fish showed a reduction of feed intake and growth rates, but they also showed a reinforced social cohesion with a well-defined endogenous swimming activity rhythm with feeding time as a main synchronization factor. The monitored decrease of the breathing/swimming activity ratio by means of the AEFishBIT data-logger also indicated a decreased energy partitioning for growth in the HD environment with a limited oxygen availability. Plasma glucose and cortisol levels increased with the rise of stocking density, and the close association of glycaemia with the expression level of antioxidant enzymes (mnsod, gpx4, prdx5) in liver and molecular chaperones (grp170, grp75) in skeletal muscle highlighted the involvement of glucose in redox processes via rerouting in the pentose-phosphate-pathway. Other adaptive features included the depletion of oxidative metabolism that favored lipid storage rather than fatty acid oxidation to decrease the oxygen demand as last electron acceptor in the mitochondrial respiratory chain. This was coincident with the metabolic readjustment of the Gh/Igf endocrinegrowth cascade that promoted the regulation of muscle growth at the local level rather than a systemic action via the liver Gh/Igf axis. Moreover, correlation analyses within HD fish, displayed negative correlations of hepatic transcripts of igf1 and igf2 with the data-logger measurements of activity and respiration, whereas the opposite was found for muscle igf2, ghr1 and ghr2. This was indicative of a growth-regulatory transition that supported a proactive instead of a reactive behavior in HD fish, which was considered adaptive to preserve an active and synchronized feeding behavior with a minimized risk of oxidative stress and epidermal skin damage.